A Content Analysis of Integrated Learning Skills & Assessment in The Textbook Entitled “Grow with English” For the Sixth Grade of Elementary School - Paulus Sainyakit (Universitas Muhammadiyah Kalimantan Timur, 2022)
Textbook helps the teachers to prepare the lessons. It is also course book used by teachers and students in order to facilitate the teaching – learning process. In terms of its role in learning, it is crucial in teaching and learning process. Related to textbooks, there should be covered by all learning skills and assessment in order to help the students to improve their ability in learning English. This research is aimed (1) to analyze all four learning skills in the textbook, (2) to find out the way four learning skills are implemented, (3) to investigate whether the textbook provides the assessment for students or not in the textbook Entitled “Grow with English” for The Sixth Grade of Elementary School. This research is included as qualitative research design. The sample of this research is an English textbook entitled “Grow with English”. The researcher uses the checklist as the instrument. In collecting and analyzing the data, the researcher does several steps. After that, the data would be calculated by using a formula. The results show that the textbook provided all learning skills differently. For the assessment, it was found that the textbook provided assessment every three chapters. In conclusion, the authors of English textbooks should implement all learning skills every chapter and the assessment at the end of every chapter in the textbooks